2002
DOI: 10.1051/0004-6361:20021446
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved, multi-color photometry and spectroscopy of Virgo 4 (OU Vir): A high orbital inclination, short orbital period dwarf nova

Abstract: Abstract. We present multi-color photometry and time resolved spectroscopy of OU Vir. The analysis of the quiescent light curve shows that OU Vir is characterized by i) strong cycle-to-cycle brightness variations, and ii) hot spot modulated light curve with grazing eclipse of the impact region. Colors are derived both in-and out-of eclipse. The time-resolved spectroscopy allows us to produce the radial velocity curve from the Hα accretion disk emission line which possibly reveals only weak evidence for hot spo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…OU Vir was observed during descent from superoutburst in both 2002 and 2003. Mason et al (2002) found that for OU Vir out of eclipse and during quiescence, V = 18.08 and B − V = 0.14, which corresponds to g ′∼ 0.2 mJy (Smith et al 2002). Vanmunster et al (2000) quote an outburst amplitude of approximately 4 mag (corresponding to a peak g ′ flux of ∼8.4 mJy).…”
Section: Light‐curve Morphologymentioning
confidence: 99%
See 2 more Smart Citations
“…OU Vir was observed during descent from superoutburst in both 2002 and 2003. Mason et al (2002) found that for OU Vir out of eclipse and during quiescence, V = 18.08 and B − V = 0.14, which corresponds to g ′∼ 0.2 mJy (Smith et al 2002). Vanmunster et al (2000) quote an outburst amplitude of approximately 4 mag (corresponding to a peak g ′ flux of ∼8.4 mJy).…”
Section: Light‐curve Morphologymentioning
confidence: 99%
“…OU Vir is a faint ( V ∼ 18; Mason et al 2002) eclipsing CV with a period of 1.75 hr which has been seen in outburst and probably superoutburst (Vanmunster, Velthuis & McCormick 2000), marking it as an SU UMa dwarf nova. Mason et al (2002) presented time‐resolved, multicolour photometry and spectroscopy of OU Vir, concluding that the eclipse is of the bright spot and the disc, but not of the white dwarf. In this paper, we present light curves of OU Vir, obtained with ULTRACAM, an ultra‐fast, triple‐beam CCD camera; for more details, see Dhillon & Marsh (2001); Dhillon et al (in preparation).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The light curve for V446 Her shows a brightening in all three bands, followed by a sudden drop. The morphology and amplitude of these variations are very similar to those seen in the optical light curves of OU Vir (Mason et al 2002). Mason et al explain those light curves by invoking a high inclination system (60 • ≤ i ≤ < 70 • ) with a large, optically thick accretion disk hot spot.…”
Section: The Light Curves Of V1974 Cygni V446 Herculis Qv Vulpeculae ...mentioning
confidence: 54%
“…This hotspot is where the accretion stream from the secondary impacts the disk. These spots typically have temperatures of 20,000 K, and can produce modulations on order of ±50% in visible bandpasses (Mason et al 2002). Because this feature is on the outer edge of the disk, it has the potential to distort the reflex motions in systems where it is prominent.…”
Section: Sco X-1mentioning
confidence: 99%